Peningkatan Kemampuan Pemecahan Masalah Penjumlahan Dan Pengurangan Siswa Kelas II SD Menggunakan Math Puzzle Games - Futry Ayu Lestari, Futry; Iwan Kuswidi; Ahmad Syawal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the improvement of addition and subtraction problem solving abilities of grade II students of SDN 1 Lalonggasumeeto through Math Puzzle Games using a quasi-experimental method with a pretest and posttest control group design, the subjects in this study were grade II students of SDN 1 Lalonggasumeeto. The results showed that students' addition and subtraction mathematical problem solving abilities through Math Puzzle Games were higher than the group that was not given treatment.